2018
DOI: 10.1099/mic.0.000673
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of colonization-defective Escherichia coli mutants reveals critical requirement for fatty acids in bacterial colony formation

Abstract: Most bacterial cells in nature exhibit extremely low colony-forming activity, despite showing various signs of viability, impeding the isolation and utilization of many bacterial resources. However, the general causes responsible for this state of low colony formation are largely unknown. Because liquid cultivation typically yields more bacterial cell cultures than traditional solid cultivation, we hypothesized that colony formation requires one or more specific gene functions that are dispensable or less impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Secondly, viable but nonculturable (VBNC) L. pneumophila on agar plates may be able to reproduce in Legiolert liquid medium. Nosho et al (2018) showed the presence of Escherichia coli that cannot form colonies on agar plates but grows only in liquid medium. Thus, there may be L. pneumophila that grow well in the liquid medium but not on agar plates.…”
mentioning
confidence: 99%
“…Secondly, viable but nonculturable (VBNC) L. pneumophila on agar plates may be able to reproduce in Legiolert liquid medium. Nosho et al (2018) showed the presence of Escherichia coli that cannot form colonies on agar plates but grows only in liquid medium. Thus, there may be L. pneumophila that grow well in the liquid medium but not on agar plates.…”
mentioning
confidence: 99%
“…The defects of the bb0562 mutant clones were the most pronounced for spirochetes in mid-log and early stationary phase ( S5 Fig ). Recently, bacterial colony formation in solid media has been linked to fatty acid availability [ 37 ]. Because the B .…”
Section: Resultsmentioning
confidence: 99%
“…E . coli lacking the fabA gene, which is essential for biosynthesis of long chain unsaturated fatty acids, is highly attenuated for colony formation on solid media under fatty acid limited conditions [ 37 ]. However, this phenotype is less pronounced for growth in liquid media, suggesting that fatty acids are particularly important for bacterial colony formation in vitro [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strongest impact might be through the change from liquid to solid cultivation conditions. Large differences in culturability for several known strains and isolation campaigns have been described depending on the choice of liquid or solid cultivation media [51][52][53].…”
Section: Discussionmentioning
confidence: 99%